1997
DOI: 10.1136/gut.40.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil cytoplasm autoantibodies against bactericidal/permeability-increasing protein in inflammatory bowel disease.

Abstract: Background-Bactericidallpermeability-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 22 publications
2
49
0
Order By: Relevance
“…The role of BPI is highlighted in that it binds to LPS with a high affinity, thereby preventing formation of the LBP-LPS complex and markedly decreasing the proinflammatory effects of endotoxin. tory bowel disease (39) which is associated with anti-BPI antibodies in perinuclear antineutrophil cytoplasmic antibodypositive ulcerative colitis (48). Anti-BPI antibodies have also been detected in patients with cystic fibrosis (60).…”
Section: Activity In Biologic Fluidsmentioning
confidence: 99%
“…The role of BPI is highlighted in that it binds to LPS with a high affinity, thereby preventing formation of the LBP-LPS complex and markedly decreasing the proinflammatory effects of endotoxin. tory bowel disease (39) which is associated with anti-BPI antibodies in perinuclear antineutrophil cytoplasmic antibodypositive ulcerative colitis (48). Anti-BPI antibodies have also been detected in patients with cystic fibrosis (60).…”
Section: Activity In Biologic Fluidsmentioning
confidence: 99%
“…This implies that data on the specificity of the antibodies studied are incomplete. One study reported anti-BPI and anti-cathepsin G antibodies in a substantial number (Ն20%) of infectious enteritis cases (26 ). Direct comparison of the sensitivities and specificities of the serologic markers described in the various studies was not possible because no ROC curves could be constructed based on the data provided in the different reports.…”
Section: Autoantigens Recognized By Autoantibodies To Neutrophils (Atmentioning
confidence: 99%
“…Overviews of the various studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) ) that have attempted to identify the antigenic species recognized by atypical P-ANCAs in UC and CD patients and in controls are given in Tables 1 through 3. The antigens that have been studied are located in the granules, the cytosol, and/or the nuclei or nuclear periphery.…”
Section: Autoantigens Recognized By Autoantibodies To Neutrophils (Atmentioning
confidence: 99%
“…Autoimmune mechanisms may play an important role in the pathogenesis of this disease. Various kinds of autoantibodies, such as anti-neutrophil cytoplasmic antibodies [1][2][3][4] and antitropomyosin antibodies, [5][6][7] have been demonstrated in serum samples of patients with ulcerative colitis.…”
Section: Introductionmentioning
confidence: 99%